2010
DOI: 10.1016/j.pec.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of physical activity promotion by smoking cessation advisors as an aid for quitting: Support for the Transtheoretical Model

Abstract: Practice Implications: PA promotion among smoking cessation advisors may be facilitated by enhancing self-efficacy, outcome efficacy and pro and con-beliefs related to PA promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…This complements the finding that advisors who are more physically active are more likely to promote PA as a cessation aid (Everson et al, 2010).…”
Section: Tailoring To the Individualsupporting
confidence: 68%
See 1 more Smart Citation
“…This complements the finding that advisors who are more physically active are more likely to promote PA as a cessation aid (Everson et al, 2010).…”
Section: Tailoring To the Individualsupporting
confidence: 68%
“…There is growing interest in PA as an aid for smoking cessation and some evidence for its effectiveness (Ussher et al, 2008), and a national survey of 170 smoking cessation advisors revealed that 56% of advisors promote PA as a strategy to help smokers quit (Everson, Taylor & Ussher, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional survey the negative association between PA and smoking was mediated by having a physically active identity. 37 Thus, by simply increasing PA there may be implicit positive effects on smoking habits.…”
Section: Possible Mechanisms For How Exercise Might Influence Smokingmentioning
confidence: 99%
“…Increasing PA prior to any quit attempt (planned or otherwise) may address concerns about simultaneous health behaviour changes. Indeed NHS guidance for stop smoking advisors is to avoid changing diet and exercise during a quit attempt [4] , and as a result advisors generally spend little time promoting PA [37] , although recent evidence suggests that simultaneous health behaviour changes may not be detrimental [38] . However, a sample of advisors who did advocate simultaneous health behaviour changes had developed integrated strategies for using one behaviour change to positively support a quit attempt (Taylor et al, in press).…”
Section: Chronic Effects Of Exercise As An Aid To Smoking Cessationmentioning
confidence: 99%
“…In addition, the findings may help practitioners prescribe PA more effectively to smokers attempting to quit. A survey of 170 Stop Smoking Service advisors in the UK revealed that 56% reported promoting PA for craving management (Everson et al 2010). This paper aims to address these issues using IPD metaanalysis methods.…”
Section: Introductionmentioning
confidence: 99%